A comparative analytical study of selected attributes of four brands of vienna sausage - Sy, Carmencita N.; Del Valle, Mercedita (1978.)
A comparative analysis of four brands of canned vienna sausage was undertaken using chemical and objective tests as well as sensory evaluation. The chemical analysis covered tests on residual nitrite, binder quantity, protein content, fat content and moisture content. The objective test for color was done using the Munsell color system. A fruit puncture tester was employed for objective measurement of texture. The subjective evaluation of color, flavor, and texture plus general acceptability was done with the help of a 64-member panel. Results of the study showed that all four brands satisfied the FDA regulation on residual nitrite but were found to fall short of the standard composition on protein and moisture contents. Three brands were observed to comply to the standard proximate composition on fat content. Two out of the four brands were found to conform with the Federal Meat Inspection regulation of the United States regarding the extent of use of binders in sausage products. Objective tests on color and textural qualities of the products were supported by findings from the subjective evaluation. Results of the general acceptability test were found to be related to some extent to the findings from the chemical analyses.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Sausages